Bioactivity-Guided Isolation of Cytotoxic Compounds from Garcinia Urophylla - Mohd Khalid, Rozida (2006)
From a selective cytotoxic activity screening program on fifteen species of plants using MTT cytotoxic assay,Garcinia urophylla showed the most potent cytotoxic activity.The methanolic extract was tested on MCF-7 cells (hormone dependent breast cancer cell line),and showed the IC50 of 2.7 ,g/mL.Garcinia urophylla or locally known as “Kandis hutan”,is a small fruiting tree usually scattered through out the hills in Malaysia and Sumatra.Up to now, there have not been any studies conducted on Garcinia urophylla.The methanolic extract of Garcinia urophylla was fractionated into hexane,dichloromethane (CH2Cl2),ethyl acetate (EtAOc) and butanol (BuOH) fractions.The fractions were tested for cytotoxic activity, and CH2Cl2 extract was found to be the most active, with IC50 = 3 ,g/mL. The active CH2Cl2 fraction gave 7 compounds including lupeol (57), gaudichaudione H (58), nor-deoxymorellin (59), 1,2,5-trihydroxy-3-methoxy-4-(3-methyl-2-butenyl)xanthone (60), 1,7-dihydroxy-3-methoxy-2-(3-methyl-2-butenyl)xanthone (62), 1,5-dihydroxy-3-methoxy-2-(3-methyl-2-butenyl)xanthone (63)and 1,3,7-trihydroxy-2-(3-methyl-2-butenyl)xanthone (64).All compounds except for lupeol showed cytotoxic activity (IC50 < 100ug/ml) towards MCF-7. The IC50 values on MCF-7 for each compounds are; > 100 ,g/ml for 57, 3.7 ± 0.7 ,g/ml for 58, 25.0 ± 4.9,g/ml for 59, 22.6 ± 4.1 ,g/ml for 60, 21.6 ± 3.4 ,g/ml for 62, 2.0 ± 0.5 ,g/ml for 63 and 5.5 ± 2.4 ,g/ml for 64. The potent activity of compound 63 and 64 was probably due to the presence of a prenyl group at C-2 and has oxygen-linked substituents at C-1 and C-3.This structure activity relationship was modified from Ito et al. (2003), which stated that the essential feature for the activity of the xanthones is the presence of two prenyl side chain at C-2 and C-8 positions in a xanthone skeleton that has oxygen-linked substituents at C-1, C-3, C-6 and C-7. Compound 59 was a new caged structure xanthonoid, due to a hydroxyl group at C-7. Compound 60 was a new tetraoxygenated xanthone due to occurrence of hydroxyl group at C-1, C-2 and C-5 and a methoxyl group at C-3